Bioethics in the wood forestry harnessing and its impact on the fauna - Arce Rojas, Rodrigo (2020)
This article aims to reflect on the scopes of bioethics in the commercial wood exploitation from tropical natural forest concerning their impacts on wildlife. To this end, a bibliographic review is carried out and a reflection is made in the light of bioethics and bio development proposals. It has been found that in certified forestry operations that are carried out at low intensity, the impacts on wildlife are minimal. Nevertheless, there are also limitations in terms of the scientific basis and methodological consistency of the assessments, which is why more rigorous systematic studies with greater temporal scope. Until now, forest management is based on a disjunctive ontological paradigm that separates human beings from nature and considers the forest as a source of forest products and opportunities for generating economic income, even though they have advanced significantly at the legal and technical levels in terms of conservation concepts, which translate into different degrees of commitment to wildlife. However, the evaluation of wildlife for its intrinsic values is almost non-existent